1996
DOI: 10.1111/1523-1747.ep12363000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Desmosomal Cadherin–Adhesive Function and Stoichiometry of Desmosomal Cadherin-Plakoglobin Complexes

Abstract: Desmosomes are intercellular adhesive junctions that associate with the intermediate filament cytoskeleton. The two major classes of transmembrane desmosomal glycoproteins, desmogleins and desmocollins, are widely considered to function as adhesion molecules. This assumption is based in part on their homology to the cadherin family of calcium-dependent homophilic adhesion molecules. In addition, autoantibodies from pemphigus patients bind directly to desmoglein family members and are thought to cause epidermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 56 publications
4
64
0
Order By: Relevance
“…In addition, all three catenins, ␣-catenin, ␤-catenin and p120 ctn , were detected in the LNER cells, and no significant difference was seen in the levels or molecular weights of these catenins when comparing the LNER cells treated or not with 4OHT. Plakoglobin was not detected (data not shown), consistent with its reported absence in L cells (Kowalczyk et al, 1996). Together, our data indicated that the cellular level of NcadER and catenins in LNER cells was not altered by 4OHT.…”
Section: Characterization Of L Cells Expressing the Ncadherin/er-lbd supporting
confidence: 88%
“…In addition, all three catenins, ␣-catenin, ␤-catenin and p120 ctn , were detected in the LNER cells, and no significant difference was seen in the levels or molecular weights of these catenins when comparing the LNER cells treated or not with 4OHT. Plakoglobin was not detected (data not shown), consistent with its reported absence in L cells (Kowalczyk et al, 1996). Together, our data indicated that the cellular level of NcadER and catenins in LNER cells was not altered by 4OHT.…”
Section: Characterization Of L Cells Expressing the Ncadherin/er-lbd supporting
confidence: 88%
“…Biochemical data confi rmed these predictions. Specifi cally, desmoplakin anchored intermediate fi laments Kouklis et al, 1994;Bornslaeger et al, 1996;Meng et al, 1997); plakophilins, plakoglobin, and desmoplakin bound each other to form a plaque (Chen et Kowalczyk et al, 1997;Bornslaeger et al, 2001), and interactions mediated by plakoglobin and plakophilin linked the plaque-fi lament complex to transmembrane, desmogleins, and desmocollins (Smith & Fuchs, 1998;Chen et al, 2002;Bonne et al, 2003;Hatzfeld et al, 2000;Kami et al, 2009;Troyanovsky et al, 1994a, 1994b, Kowalczyk et al, 1996Witcher et al, 1996;Choi et al, 2009;Mathur et al, 1994;Roh & Stanley, 1995;Kowalczyk et al, 1999;Andl & Stanley, 2001;Bornslaeger et al, 2001;Gaudry et al, 2001). The ability of desmosomal cadherins to establish trans interactions between cells, in turn, accounted for the actual adhesive bond formed between two cells (Waschke et al, 2007;Nie et al, 2011;Chitaev & Troyanovsky, 1997;Aoyama et al, 2009).…”
Section: Assembly : Intradesmosomal Protein Interactionsmentioning
confidence: 99%
“…org). At the extreme, desmoplakin, a component of desmosomal tight junctions in peripheral tissues (Kowalczyk et al, 1996), is completely restricted to granule cells of the dentate gyrus, both within the hippocampus ( Fig. 2A,F) and throughout the entire brain (supplemental Fig.…”
Section: Definition Of Boundaries Between Hippocampal Subregionsmentioning
confidence: 99%
“…These characteristics are presumably attributable to expression of cytoskeletal proteins and ion channels, a number of which display striking region-specific expression. For example, desmoplakin, known as a component of desmosomal plaques (Kowalczyk et al, 1996), is expressed solely in the dentate gyrus. Granule cell axons, the so-called "mossy fibers," have a very distinctive morphology with extremely large terminal endings characterized by rows of puncta adherens (Claiborne et al, 1986;Acsady et al, 1998).…”
Section: Gene Expression and Hippocampal Cytoarchitecturementioning
confidence: 99%